Gojek As A Digital Economy Enabler: A Case Study On Its Role For Partner Drivers And Msmes In Indonesia - Ayundasari, Catleya; Audrew, Edelweis; Birkenbach, Parker Adam (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
In recent years, Indonesia has witnessed rapid digital transformation across various sectors, with digital platforms emerging as key drivers of economic inclusion and innovation. This paper explores Gojek’s role as a digital enabler that bridges the gap between technology and underserved communities, focusing on in what ways it has been helping its partner drivers and micro, small, and medium enterprises (MSMEs). Using a qualitative case study approach, this research analyzes how Gojek’s technological ecosystem including its super app, GoPay integration, and partner training programs has empowered individuals and small businesses to thrive in an increasingly digital economy. The findings highlight three key areas: (1) how Gojek’s platform facilitates access to a wider customer base and digital payment infrastructure for MSMEs; (2) the socio-economic upliftment of driver-partners through digital literacy and income diversification; and (3) the broader implications for inclusive growth in urban and peri-urban areas. By showcasing real stories and data from Gojek’s ecosystem, this paper offers practical insights into how digital transformation, when designed with inclusivity at its core, can create meaningful economic opportunities. It concludes by reflecting on the challenges and potential scalability of such models across Southeast Asia and other emerging markets.